Two Dominant Herbaceous Species Have Different Plastic Responses to N Addition in a Desert Steppe - Guo, Aixia; Zuo, Xiaoan; Hu, Ya; Yue, Ping; Li, Xiangyun; Lv, Peng; Zhao, Shenglong (Frontiers in Plant Science, 2022)
Nitrogen (N) deposition rates are increasing in the temperate steppe due to human activities. Understanding the plastic responses of plant dominant species to increased N deposition through the lens of multiple traits is crucial for species selection in the process of vegetation restoration. Here we measured leaf morphological, physiological and anatomical traits of two dominant species (Stipa glareosa and Peganum harmala) after three-year N addition (0, 1, 3, 6 g N m−2 year−1, designated N0, N1, N3 and N6, respectively) in desert steppe of Inner Mongolia. We separately calculated the phenotypic plasticity index (PI) of each trait under different N treatments and the mean phenotypic plasticity index (MPI) of per species. The results showed that N addition increased the leaf N content (LNC) in both species. N6 increased the contents of soluble protein and proline, and decreased the superoxide dismutase (SOD) and the peroxidase (POD) activities of S. glareosa, while increased POD and catalase (CAT) activities of P. harmala. N6 increased the palisade tissue thickness (PT), leaf thickness (LT), and palisade-spongy tissue ratio (PT/ST) and decreased the spongy tissue–leaf thickness ratio (ST/LT) of S. glareosa. Furthermore, we found higher physiological plasticity but lower morphological and anatomical plasticity in both species, with greater anatomical plasticity and MPI in S. glareosa than P. harmala. Overall, multi-traits comparison reveals that two dominant desert-steppe species differ in their plastic responses to N addition. The higher plasticity of S. glareosa provides some insight into why S. glareosa has a broad distribution in a desert steppe.